Rehabilitation effects of land and water-based aerobic exercise on lung function, dyspnea, and exercise capacity in patients with chronic obstructive pulmonary disease: A systematic review and meta-analysis. Issue 33 (20th August 2021) - Chen, Haixia; Li, Peijun; Li, Ning; Wang, Zhengrong; Wu, Weibing; Wang, Jihong
Abstract: Background: We sought to synthesize the evidence about aerobic exercise intervention during pulmonary rehabilitation, and to further explore the difference in rehabilitation effects between water and land-based aerobic exercise. This review's purpose is to provide a basis by which practitioners and therapists can select and create appropriate therapeutic programs. Methods: Data of randomized and quasi-randomized controlled trials comparing training group (TG, aerobic exercise in water or land) and control group (CG, usual care) in chronic obstructive pulmonary disease (COPD) patients (January 1, 2000–December 28, 2019) were obtained from the Cochrane Library, PubMed, Embase, China National Knowledge Infrastructure, and Wanfang databases. Two researchers independently reviewed the literature, extracted the data, and evaluated the quality of the literature. Review Manager software (Rev Man 5.3; Cochrane, London, UK) was used for meta-analysis. The rehabilitation effect of water- or land based aerobic exercise was evaluated by subgroup analysis. The proposed systematic review details were registered in PROSPERO (CRD 42020168331). Results: Eighteen studies (1311 cases of COPD) were included. Meta-analysis results show that compared with the control group, the dyspnea level and functional and endurance exercise capacity in COPD patients were significantly improved after aerobic exercise ( P < .05), but there was no significant change in lung function ( P > .05). Compared with land-based aerobic exercise, water-based aerobic exercise significantly improved the endurance exercise capacity in COPD patients (mean difference [MD]: 270.18, 95% CI: 74.61–465.75). Conclusion: Medium to high-quality evidence shows that aerobic exercise can effectively improve dyspnea and exercise capacity in COPD patients. Compared with land-based aerobic exercise, water-based aerobic exercise had a significant additional effect in improving the endurance exercise capacity of COPD patients.